Validity of the Ethics Assessment Instrument for Senior High School Students - Sun'an, Ulin Nuha; Isnaeni, Wiwi; Khumaedi, Muhammad (Journal of Research and Educational Research Evaluation, 2024)
Proving the validity of research instruments is very important. The success of research is largely determined by the validity or invalidity of the instruments used. The validity of the instrument greatly affects the accuracy of the measurement results. The basic principle of research instruments is to measure what will be measured. The purpose of proving the validity of the instrument is to ensure that the instrument reflects the theoretical concept. Proof of validity in this study includes instrument content validity, item validity, construct validity. Proof of content validity using the Aiken V formula. This research involved 7 expert judgements to validate the developed ethics instrument. The results of data analysis obtained the coefficient value V is valid. Proof of item validity using the pearson correlation product moment formula with the criteria r count> r table. The study involved 386 students so that the criterion r count> 0.113 with a significance of 0.05. Proof of construct validity using the exploratory factor analysis method and all items are valid by obtaining a KMO value of 0.811> 0.5 and each item obtains an anti-image correlation value> 0.5 and based on the analysis of Initial Eugenvalues Comulative terbahadap 20 statement items obtained five components whose value is > 1.